2010
DOI: 10.1093/jla/2.2.621
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Universal Health Insurance on Malpractice Claims: The Japanese Experience

Abstract: Japanese patients file relatively few medical malpractice claims. Most scholars try to explain this phenomenon by identifying ''faults'' in the Japanese judicial system. Largely, the faults they identify do not exist. Instead, a substantial part of the reason for the malpractice claiming patterns may lie in the national health insurance system. In order to contain the cost of this system, the government suppresses the price it pays for the technologically most sophisticated procedures. Predictably as a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Both coverage rate of UEBMI and URBMI were negatively associated with the malpractice lawsuits, but only statistically signi cant for coe cients for UEBMI. Ramseyer (2009) [34]found that universal health insurance system in Japan prompted the government to cover the rudimentary health services and suppressed the price for sophisticated procedures. Hence, it was possible that the medical malpractices showed a decreasing trend because patients were less likely to sue over primary health care.…”
Section: Resultsmentioning
confidence: 99%
“…Both coverage rate of UEBMI and URBMI were negatively associated with the malpractice lawsuits, but only statistically signi cant for coe cients for UEBMI. Ramseyer (2009) [34]found that universal health insurance system in Japan prompted the government to cover the rudimentary health services and suppressed the price for sophisticated procedures. Hence, it was possible that the medical malpractices showed a decreasing trend because patients were less likely to sue over primary health care.…”
Section: Resultsmentioning
confidence: 99%
“…Each year, only 1,100 Japanese file medical malpractice suits either. 19 Again, the substantive law is close to that in the U.S. Median damage awards are close.…”
mentioning
confidence: 79%
“…According to Ramseyer (2010), physicians in Japan have been facing increasing risks in malpractice claims. Among all malpractice claims, 46.3 % are surgery related.…”
Section: Japanmentioning
confidence: 99%